If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10n + 7 = 13 Reorder the terms: 7 + 10n = 13 Solving 7 + 10n = 13 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 10n = 13 + -7 Combine like terms: 7 + -7 = 0 0 + 10n = 13 + -7 10n = 13 + -7 Combine like terms: 13 + -7 = 6 10n = 6 Divide each side by '10'. n = 0.6 Simplifying n = 0.6
| 8x+60=68 | | -10=-6-m | | 12=-2b | | (75x+50)=(25+70)x | | -4x^2+2x-7=0 | | 4u+12=44 | | 24x^2+22x=21 | | -6a+13=19 | | 2h^2+h+14=y | | 5a-5=9-2a | | 16-3m=-2 | | -100k+-30=-75-50k | | 6x+6x^2=12 | | (-7x^4y)(5x^2+9x^6y^3-3y^3)= | | -6=-7-n | | 33-y=20 | | 40+3x=(5x-10) | | .50x+.25(70)=37.5 | | x-(21)=9 | | -9k=126 | | 22+y=25 | | -7x^4y(5x^2+9x^6y^3-3y^3)= | | cos(2x)*cos(4x)= | | -9=126 | | 1.2-n+3.4=10 | | 2x-53=17 | | 2=t(28-4.9t) | | 0.25x+.05(6-x)=.10(-29) | | 3n-10=56 | | 3x^2+3y^2+18x-42y+162=0 | | 42=4x+6y | | (2x^3)+16=0 |